1946
DOI: 10.3133/ofr472
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report on stratigraphy of the phosphatic shale member of the Phosphoria formation in Western Wyoming, southeastern Idaho, and northern Utah

Abstract: Character and correlation of beds of the phosphatic shale member of the Phosphoria formation, Strawberry Creek-Dry Canyon divide to Cottorwood Creek, Tffoming. in pocket Character and correlation^ of beds of the pfcosphatic v shale member of the Phosphoria formation, North Fork ?o£ Swift Creek, 1t$romin& toe the sautit end of tha I Crawfbrd Mountains, Utah ».

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1955
1955
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In general the lithology of the formation varies with the thickness. Where the formation is thick, Unit B has been designated the phosphatic shale member in the southwestern portion of the area of the report (Gardner, 1944) and is correlative with the 200 foot thick phosphatic shale member in southeastern Idaho (McKelvey, 1946). The unit probably is the correlative of unit B in southwestern Montana (Klepper and others, 1948;Cressman.…”
Section: Lithology Of the Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general the lithology of the formation varies with the thickness. Where the formation is thick, Unit B has been designated the phosphatic shale member in the southwestern portion of the area of the report (Gardner, 1944) and is correlative with the 200 foot thick phosphatic shale member in southeastern Idaho (McKelvey, 1946). The unit probably is the correlative of unit B in southwestern Montana (Klepper and others, 1948;Cressman.…”
Section: Lithology Of the Formationmentioning
confidence: 99%
“…The preservation of sediments that are formed from the hard parts of organisms would also be controlled by the physical-chemical environment; that is, if the water in which the biogenic mineral is deposited is not saturated with that mineral, it will be unstable and will tend to dissolve (McKelvey, 1946;Krumbein and Garrels, 1952).…”
Section: Elmentioning
confidence: 99%
“…CPM for the widespread Permian (Wordian) Rex Chert Member of the Phosphoria Formation (Idaho, Utah, Montana and Wyoming) accumulated in western Pangea under arid conditions when the NAC was situated between 0° and 30 N (Boucot et al, 2013, Map 15). The phosphate, chert, and other constituents in the Phosphoria Formation have been attributed to upwelling (c.f., McKelvey, 1946;Hein et al, 2004). Ketner (2009) suggested that upwelling could not have extended across the broad cratonic expanse of the Rex Chert occurrence.…”
Section: Permian Chertmentioning
confidence: 99%
“…The geographic setting of the Meade Peak Member, including its relation to upwelling, has been established by regional stratigraphic studies of the Phosphoria Formation (for example, McKelvey and others, 1959;Sheldon, 1964Sheldon, , 1981. The requisite slow deposition and circulating 'seawater are also necessary for phosphorite (McKelvey, 1946). The concentrations of vanadium in the zone are so high (locally, 150 times or more its crustal abundance of 150 g/t) (Rankama and Sahama, 1950) relative to its ordinary occurrence that they could have been attained only in the absence of the dilution that would have resulted from sedimentation at ordinary rates.…”
Section: Originmentioning
confidence: 99%
“…A black shale containing 0.8 to 0.9 percent V205 over a large area was discovered by W.W. Rubey of the U.S. Geological Survey (USGS) in 1938 in the upper part of the Meade Peak Member of the Permian Phosphoria Formation in the Salt River Range of western Wyoming (Rubey, 1943(Rubey, ,1958. This vanadiferous zone, as it came to be called informally, was sampled by the USGS in 1942 at numerous localities in the adjoining region (McKelvey, 1946); it was sampled in more detail in late 1942 and 1943 by the Wyodak Coal and Manufacturing Co., agent for the Metals Reserve Co., in the Paris-Bloomington area of Idaho (McKelvey and Strobell, 1955) and in the Sublette Ridge area of Wyoming. The U.S. Bureau of Mines (USBM) also explored the zone in Sublette Ridge (Allsman and others, 1949a) as well as in the Salt River Range (Allsman and others, 1949b) and investigated means of recovering the vanadium (Ravitz and others, 1947).…”
Section: Introductionmentioning
confidence: 99%